(3HjGf GdMGLI Edi GdWH hBOGH GdCWHGAs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s ((3LQhf s)
(3ChdgG (B:s
(3bO LQJ GdYGOI ai ahGJjM GdYdhhe HjGf TQa GdYde GdPi jTQM ajg hCjVkG s
(3BNQgG (B:s
(3hdPdc deG bjd dHhQR LegQ (B: (3MGdce dG JYGJHh GdLgGd ? bGd dCfGdG fWeY ai GdYejGf Cf jHUQhG s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcHG GdChd (B- (3U (B34 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs